A 22:1 Compression Ratio Ammonia-Hydrogen HCCI Engine: Combustion, Load, and Emission Performances - Pochet, Maxime; Jeanmart, Hervé; Contino, Francesco (Frontiers in Mechanical Engineering, 2020)
The interest in ammonia as a high-density hydrogen carrier for long-term electricity storage is growing. A clean and efficient Combined Heat and Power (CHP) system is envisioned for power production from stored ammonia, to which Homogeneous-Charge Compression-Ignition (HCCI) engines are promising. Although recent studies showed a high equivalence ratio potential for ammonia HCCI engines, its resistance to auto-ignition forces the use of high intake temperatures, which limits the engine power density. Moreover, the feasibility of clean and highly efficient ammonia combustion has not been demonstrated. Therefore an HCCI test bench has been modified to reach an effective compression ratio of 22:1, which allowed operation from neat hydrogen up to 95%vol. ammonia. A full cartography of the ammonia-hydrogen load range, related efficiencies and emissions is obtained and the impact of the equivalence ratio (from 0.1 to 0.6), the intake temperature (from 50 ◦C to 240 ◦C) and Exhaust Gas Recirculation is assessed. Thanks to a reduced combustion intensity, ammonia allows a 50% IMEP increase compared to neat hydrogen, while maintaining equivalent combustion efficiencies. Using the ammonia-hydrogen blending ratio as a control parameter, the combustion timing and load control is broadened. The EGR impact was mixed: a positive reduction of NO emissions but a negative impact on NO2 and unburned emissions. Finally, the trade-off for the ideal ammonia-hydrogen blending ratio is discussed. To optimise the concept, boosted conditions with higher stroke-to- bore ratios must be aimed at.